Spatial Planning in the Tourism Economy in the Lublin Region: Aid or Obstacle? - Waldemar Gorzym-Wilkowski (Barometr Regionalny)
Lubelskie Voivodship needs new stimuli of economic development, and tourism can be one of them. However, a chaotic development of this sector can bring short-term benefits, and it can also lead to numerous conflicts between various entities and have an adverse impact on the state of tourist assets. In consequence, the disadvantages can prevail over the advantages in the long term. Such a risk can be mitigated by spatial planning, specifically by local spatial development plans issued by local governments in communes.